Corpus of Vietnamese Orientational Metaphors "Lên" and "Xuống" - Duong Tran Van (21690608) (2025)
This dataset contains 506 metaphorical instances of the Vietnamese spatial terms lên ("up") and xuống ("down"), extracted from a private corpus hosted on VietCorpus. The dataset comprises two Excel files: one for lên (304 instances) and one for xuống (202 instances). Each entry includes the metaphorical expression, contextual sentence, connotative meaning (positive, negative, neutral), target domain, and conceptual category. This dataset supports the findings presented in the manuscript Beyond GOOD IS UP, BAD IS DOWN: Cultural Valence Inversions in Vietnamese Orientational Metaphors, submitted to Metaphor and Symbol. The data illustrates how Vietnamese orientational metaphors systematically invert universal valence patterns proposed by Conceptual Metaphor Theory, highlighting the role of cultural elaboration in shaping embodied metaphorical extensions. Author ORCID: 0009-0003-4096-850X